2016
DOI: 10.1155/2016/8173876
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe edulis Extract but Not Oil Enhances Antioxidant Defenses and Protects against Nonalcoholic Fatty Liver Disease Induced by a High‐Fat Diet in Rats

Abstract: We investigated the effects of E. edulis bioproducts (lyophilized pulp [LEE], defatted lyophilized pulp [LDEE], and oil [EO]) on nonalcoholic fatty liver disease (NAFLD) induced by a high-fat diet (HFD) in rats. All products were chemically analyzed. In vivo, 42 rats were equally randomized into seven groups receiving standard diet, HFD alone or combined with EO, LEE, or LDEE. After NAFLD induction, LEE, LDEE, or EO was added to the animals' diet for 4 weeks. LEE was rich in polyunsaturated fatty acids. From L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Studies have shown that anthocyanins have a high antioxidant capacity and activate important pathways in the fight against metabolic reactors, which highlights its importance in the fight against cellular oxidation and consequently in the pathogenesis of cardiovascular diseases, hepatic diseases, diabetes and cancer. Thus, the analysis of foods rich in these compounds has been steadily growing because dietary supplementation with tropical fruit pulp rich in antioxidants has been presented as an effective curative and preventive therapy for the treatment of several conditions associated with pathological conditions (Felzenszwalb, da Costa Marques, Mazzei, & Aiub, 2013;Freitas et al, 2016;Pereira et al, 2014;. The fruits of jussara contain two main anthocyanins identified as cyanidin 3-glucoside and cyanidin 3-rutinoside (Harborne, Saito, & Detoni, 1994), in addition to minor compounds such as cyanidin 3-sambubioside, pelargonidine 3-glycoside, cyanidin 3-rhamnoside and pelargonidine 3 rutinoside identified by LC-DAD-ESI/MS (Rufino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that anthocyanins have a high antioxidant capacity and activate important pathways in the fight against metabolic reactors, which highlights its importance in the fight against cellular oxidation and consequently in the pathogenesis of cardiovascular diseases, hepatic diseases, diabetes and cancer. Thus, the analysis of foods rich in these compounds has been steadily growing because dietary supplementation with tropical fruit pulp rich in antioxidants has been presented as an effective curative and preventive therapy for the treatment of several conditions associated with pathological conditions (Felzenszwalb, da Costa Marques, Mazzei, & Aiub, 2013;Freitas et al, 2016;Pereira et al, 2014;. The fruits of jussara contain two main anthocyanins identified as cyanidin 3-glucoside and cyanidin 3-rutinoside (Harborne, Saito, & Detoni, 1994), in addition to minor compounds such as cyanidin 3-sambubioside, pelargonidine 3-glycoside, cyanidin 3-rhamnoside and pelargonidine 3 rutinoside identified by LC-DAD-ESI/MS (Rufino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of jussara contain two main anthocyanins identified as cyanidin 3-glucoside and cyanidin 3-rutinoside (Harborne, Saito, & Detoni, 1994), in addition to minor compounds such as cyanidin 3-sambubioside, pelargonidine 3-glycoside, cyanidin 3-rhamnoside and pelargonidine 3 rutinoside identified by LC-DAD-ESI/MS (Rufino et al, 2010). The lipid fraction obtained from the pulp of jussara (although little used) is also suitable for consumption due to its high content of polyunsaturated fatty acids, remarkable concentration of oleic acid, palmitic and linoleic acids, similar to E. oleraceae, and lower saturated lipid concentration compared to other oils (Freitas et al, 2016). The saturated fatty acids present in this fruit represent 24.32-28.89% of the total lipid content (Neida & Elba, 2007;Schauss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The groups that received pulp (defatted or not) attenuated the steatosis and lipid peroxidation in tissues, while the oil did not show the same effect. The most promising product appeared to be lyophilized pulp defatted, possibly due low lipid content and high ACNs and phenols [34]. Lipids are susceptible targets of oxidation because of their molecular structure, and their peroxidation is proposed as markers of lipid damage [35].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Considering the effect of the juçara extract on lipid peroxidation, some studies have demonstrated the attenuation of this biomarker of oxidative damage [15,34,40].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Also, GP-treatment markedly decrease serum AST, ALP, insulin, and decrease the body mass index (BMI) and insulin resistance index [150]. Ombuin is a flavonoid isolated from GP showed a decrease of intracellular concentrations of triglyceride and cholesterol in liver cancer cells as well as reduce the expression of some biogenic genes through activating PPAR-α and ß/γ [151].…”
Section: Role Of Phytobioactive Compoundsmentioning
confidence: 99%